2010
DOI: 10.1515/cclm.2011.061
|View full text |Cite
|
Sign up to set email alerts
|

Determination of oxidative and occupational stress in palliative care workers

Abstract: Our findings suggest that oxidative stress, occupational stress and occupational burnout levels are similar in men and women. Occupational stress increases oxidative stress levels probably as a response to increased generation of reactive oxygen species. Working during the evening and night shifts increases oxidative levels and burnout levels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
19
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 34 publications
(37 reference statements)
4
19
1
Order By: Relevance
“…But results is in contrast with another studies which showed that MDA concentrations increased with age (31) , and SOD level decreased with age 32 . Tobacco smoke is a rich source of oxidants.…”
Section: Discussioncontrasting
confidence: 93%
“…But results is in contrast with another studies which showed that MDA concentrations increased with age (31) , and SOD level decreased with age 32 . Tobacco smoke is a rich source of oxidants.…”
Section: Discussioncontrasting
confidence: 93%
“…In human studies, significantly increased oxidative stress and decreased plasma antioxidants have been observed in university students after exposure to acute stress . Similarly, a study on palliative care workers who were exposed to occupational stress has reported significantly high MDA levels and SOD activity . None of these studies evaluated stress and oxidative stress in the context of diabetes risk.…”
Section: Discussionmentioning
confidence: 99%
“…7 Mounting evidence suggests that oxidative stress indices increase signicantly aer continuous shi work. [8][9][10][11][12] Disruptions of the normal light/dark cycle in wild-type mice can simulate disruption due to shi work in humans. 13 Intervention in oxidative status in the liver can reduce the risk of many liver diseases such as chronic hepatitis, cholestasis, and alcoholic and non-alcoholic fatty liver disease.…”
Section: Introductionmentioning
confidence: 99%